The nutritional support to prevent sarcopenia in the elderly - Giacosa, Attilio; Barrile, Gaetan Claude; Mansueto, Francesca; Rondanelli, Mariangela (Frontiers in Nutrition, 2024)
Sarcopenia has been described as a muscle disease, with multiple adverse consequences on human health. Recommendations aimed at supporting awareness, prevention, early detection and treatment of this disease are needed. This review focuses on the epidemiology, pathophysiology and early detection of elderly sarcopenia. As far as treatment is concerned, physical activity and nutritional support are specifically evaluated. An individually tailored resistance exercise training program appears to be crucial for a positive outcome of the sarcopenia prevention and treatment. The nutritional intervention is mostly based on the supplementation with high-quality proteins (i.e., whey protein) in order to increase the intake of essential amino acids and in particular of leucine. In addition, of relevant importance appears to be the supplementation with vitamin D, with omega-3 fatty acids and probiotics. This review evaluates the results of the most qualified studies on the nutritional supplementation of sarcopenic elderly subjects and shows that promising results have been achieved in community elderly subjects, or subjects followed in rehabilitation centers and in nursing homes, with additional resistance exercise programs.